Clinical profile and mortality in patients with T. cruzi/HIV co-infection from the multicenter data base of the "Network for healthcare and study of Trypanosoma cruzi/HIV co-infection and other immunosuppression conditions". - Maria Aparecida Shikanai-Yasuda; Mauro Felippe Felix Mediano; Christina Terra Gallafrio Novaes; Andréa Silvestre de Sousa; Ana Marli Christovam Sartori; Rodrigo Carvalho Santana; Dalmo Correia; Cleudson Nery de Castro; Marilia Maria Dos Santos Severo; Alejandro Marcel Hasslocher-Moreno; Marisa Liliana Fernandez; Fernando Salvador; et al. (Public Library of Science (PLoS), 2021)
Objective Chagas disease (CD) globalization facilitated the co-infection with Human Immunodeficiency Virus (HIV) in endemic and non-endemic areas. Considering the underestimation of Trypanosoma cruzi (T. cruzi)-HIV co-infection and the risk of life-threatening Chagas Disease Reactivation (CDR), this study aimed to analyze the major co-infection clinical characteristics and its mortality rates. Methods This is a cross-sectional retrospective multicenter study of patients with CD confirmed by two serological or one parasitological tests, and HIV infection confirmed by immunoblot. CDR was diagnosed by direct microscopy with detection of trypomastigote forms in the blood or other biological fluids and/or amastigote forms in inflammatory lesions. Results Out of 241 patients with co-infection, 86.7% were from Brazil, 47.5% had <200 CD4+ T cells/μL and median viral load was 17,000 copies/μL. Sixty CDR cases were observed. Death was more frequent in patients with reactivation and was mainly caused by CDR. Other causes of death unrelated to CDR were the manifestation of opportunistic infections in those with Acquired Immunodeficiency Syndrome. The time between the co-infection diagnosis to death was shorter in patients with CDR. Lower CD4+ cells count at co-infection diagnosis was independently associated with reactivation. Similarly, lower CD4+ cells numbers at co-infection diagnosis and male sex were associated with higher lethality in CDR. Additionally, CD4+ cells were lower in meningoencephalitis than in myocarditis and milder forms. Conclusion This study showed major features on T. cruzi-HIV co-infection and highlighted the prognostic role of CD4+ cells for reactivation and mortality. Since lethality was high in meningoencephalitis and all untreated patients died shortly after the diagnosis, early diagnosis, immediate antiparasitic treatment, patient follow-up and epidemiological surveillance are essentials in T. cruzi/HIV co-infection and CDR managements.